The Impact Of Technology And Artificial Intelligence On Arabic Literary Text/ أثر التقنية والذكاء الاصطناعي على النص الأدب العربي - AlMugim, Tarig Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The past twenty-five years have witnessed rapid technological developments that have significantly affected the reception and interaction with literature, and the structure of literary genres has been affected by this technology. Among the most prominent literary genres affected by this technology are poetic poems, as we see a lack of long poems during that period. This technology seemed neutral towards the novel and could not affect the nature of its structure. Many poetic poems were accompanied by music and various sound effects, which negatively affected the poet's interest in the internal music of the text. This technology contributed to the creation of literary forms such as the tweet. Also, it allowed the emergence of the art of the very short story. Artificial intelligence literature recently appeared in the previous period, but it did not significantly impact literary texts. However, critics differed on the extent of its effects in the future and that it will be affected by the inputs that are relied upon to produce the text. These inputs and software are initially affected by several factors, such as the era's nature and the difference in the environment. It will also be affected by the nature of the blogs that will be relied upon in training the machine that generates texts. Critics also warned of the need to monitor the ideas, texts and values produced by artificial intelligence, as its danger lies in the ideas of its producers and the texts it was trained on, which will often have a rational tendency to sanctify the machine and relies on the human being who is identified with technology regardless of his humanity, values, history and language. Critics also pointed out that the experiments of artificial intelligence in literature are not far from their experiments in other fields of creativity, such as media and others.